A study on training factors and its impact on training effectiveness towards technical workers in Panasonic System Network Malaysia / Farahana Mohani - Mohani, Farahana (Faculty of Business and Management, 2014)
The main objectives of this study is a study on training factors and its impact on training effectiveness towards technical workers in Panasonic System Network Malaysia. The variables examined were demographic characteristics ( age, gender, marital status, education level and length of working experiences), training environment and work environment. A total of 113 questionnaire were distribute to the respondent in Panasonic System Network Malaysia (PSNM) company. This study was designed to identify through questionnaire survey that can contribute towards training effectiveness. The result of study found that training environment and work environment significantly affect training effectiveness. Therefore, the training environment and work environment have a relationship with the training effectiveness.